ANALISIS ALTERNATIF DESAIN BANGUNAN JEMBATAN DENGAN VALUE ENGINEERING - Busri, M. Hasan (EXTRAPOLASI, 2014)
Planning or design phase of the bridge construction project is often not optimal, which affects the amount of waste and unnecessary costs of the construction phase of the bridge so that the application of Value Engineering efforts could be a solution to optimize the value of the benefits while reducing costs unnecessary.Â  Besides, designs and models of various bridge today requires us to be able to choose a model which bridges the most suitable and appropriate to the local natural conditions. This study was conducted to determine the structure of the bridge what is the most economical but still complied with the required strength. The bridge was built with spans of 40 m and a width of 7 m is equipped with 2 (two) sidewalk on the right and left. In this study, the analysis will be conducted on three types of bridges, namely precast bridge, bridge and bridge betonkonvensional steel frame. The method used is a value engineering analysis of the four models that will bridge over the pre-cast bridge, bridge frame of steel and conventional concrete bridge. In the value engineering method (value engineering), there are several steps that must be done is the information phase, the analysis phase function, the creative stage and phase of development. Â The results showed that of the three (3) alternative bridge is a conventional concrete bridge, precast concrete bridge, and the bridge framework. Obtained by a conventional concrete bridge structures bridge the most economical, while for bridge steel frame and precast concrete bridge as an alternative.Keywords: Value Engineering, Bridge Building Structure, cost efficiency